(untitled) (Barqaror Taraqqiyot va Rivojlanish Tamoyillari, 2023)
In this article, in the organization of pedagogical education, the mastery level of students and their acceptance of psychological theories of knowledge, cognitive characteristics are of great importance. In this, it is explained that in working with young students, their level of mastery is carried out organically with the psychology of youth. In the organization of qualityeducation, acceptable and necessary educational conditions are determined for them, while ensuring the interrelationship and coherence of various standards and state educational standards.